Majid Arslan and His Role in Forming the Lebanese National Guard Assoc. - Latif , Dr. Qasim Jabari (Thi Qar Arts Journal, 2024)
This research aims to study the life of the deputy and minister Majid Arslan and his role in Lebanese politics, specifically his role in forming the Lebanese National Guard. We chose this figure due to the significant role he played as one of the first-generation men who witnessed the political events in Lebanon, fighting against the French occupation and achieving complete independence and evacuation from Lebanese lands. Through detailing his political role, we tried to trace the precise historical developments he went through, starting from his birth and upbringing, then his tenure as a deputy and minister. The focus was on the major task he undertook, which was leading the Lebanese National Guard, which was formed, organized, and armed under his direct supervision. These forces played a notable role in confronting the French forces during the clashes in the Bshamoun area. From all this, it became clear to us that he was a distinguished and competent figure who played an important and active role in a significant phase of modern and contemporary Lebanese political history.